2020
DOI: 10.1037/ccp0000455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modifying interpretation bias on transdiagnostic repetitive negative thinking.

Abstract: Repetitive negative thinking (RNT; e.g. worry and rumination) is common across emotional disorders, as is the tendency to generate negative interpretations (interpretation bias).Ameliorating negative interpretations via cognitive bias modification of interpretations (CBM-I) reduces worry/rumination, and improves mood in people diagnosed with GAD or Depression.We investigated whether these findings generalize to high worry or rumination populations, irrespective of diagnosis, and whether effects are increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…However, research using “cognitive bias modification” paradigms to train a certain interpretive style has found that changing interpretation bias may lead to corresponding changes in worry (Hayes et al, 2010; Hirsch et al, 2009) and rumination (Hertel et al, 2014, Experiment 2), supporting a causal link between interpretation bias and repetitive negative thinking and indicating that interpretation bias is not a result or concomitant of worry and rumination. Indeed, the longer term effects of changing interpretation bias on worry and rumination are now being explored (Hirsch et al, 2018, 2019; Krahé, Mathews, Whyte, & Hirsch, 2016). Nevertheless, this article provides novel and much needed cross-sectional evidence for the relationship between interpretation bias and levels of both worry and rumination and constitutes the first study in adults to demonstrate that worry is correlated with negative interpretation bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, research using “cognitive bias modification” paradigms to train a certain interpretive style has found that changing interpretation bias may lead to corresponding changes in worry (Hayes et al, 2010; Hirsch et al, 2009) and rumination (Hertel et al, 2014, Experiment 2), supporting a causal link between interpretation bias and repetitive negative thinking and indicating that interpretation bias is not a result or concomitant of worry and rumination. Indeed, the longer term effects of changing interpretation bias on worry and rumination are now being explored (Hirsch et al, 2018, 2019; Krahé, Mathews, Whyte, & Hirsch, 2016). Nevertheless, this article provides novel and much needed cross-sectional evidence for the relationship between interpretation bias and levels of both worry and rumination and constitutes the first study in adults to demonstrate that worry is correlated with negative interpretation bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CBM for interpretation that is enhanced with prolonged imagery and self-generation of outcomes may be particularly helpful in this regard, in a similar manner to using interventions in CBT that target multiple cognitive biases simultaneously. 102) has shown that interpretation training enhanced in this manner augments impact on interpretation bias and could be a promising form of CBM to incorporate into cognitive-process-focused CBT for GAD. Further investigation of clinical outcomes for CBT for GAD incorporating these CBM with imagery and self-generation of outcome is indicated, particularly to determine if this could make face to face CBT briefer.…”
Section: Discussionmentioning
confidence: 99%
“…Scrambled Sentences Test (SST) -This task was employed by Hirsch et al (2018) and Hirsch, Krahé, Whyte, Bridge, et al (2020), adapted from Wenzlaff and Bates (1998, no grammatically correct sentences in the Scrambled Sentences Test. Seven pregnant and three non-pregnant participants were removed from analysis.…”
Section: Interpretation Measuresmentioning
confidence: 99%
“…Materials included items related to two themes -pregnancy related and general (non-pregnancy) related. General materials were drawn from worry and rumination recognition test materials used by Hirsch, Krahé, Whyte, & Bridge, et al (2020), while the pregnancy materials were developed for the current study from interviews with four pregnant women 3 . The RT has two phases: in the first, participants read 21 ambiguous scenarios and answered a comprehension question after each scenario.…”
Section: )mentioning
confidence: 99%